2017
DOI: 10.3414/me17-05-0003
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Application Areas and Technology Combinations

Abstract: SummaryBackground: With the continuous and enormous spread of mobile technologies, mHealth has evolved as a new subfield of eHealth. While eHealth is broadly focused on information and communication technologies, mHealth seeks to explore more into mobile devices and wireless communication. Since mobile phone penetration has exceeded other infrastructure in low and middle-income countries (LMICs), mHealth is seen as a promising component to provide pervasive and patient-centered care.Objectives: The aim of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 245 publications
4
75
0
2
Order By: Relevance
“…Evidence suggests that using both approaches together (standard surveillance methods (traps) and mobile apps) are effective as entomological surveillance instruments for decisionmaking in the control of Aedes mosquitoes and subsequent action. Our review shows that the most dominant purpose is surveillance while research on management of arboviral disease is limited which is consistent with another review (Abaza and Marschollek, 2017). However, we also observed an increasing interest in the use of mobile phones addressed to diagnose arboviral diseases in the last three years.…”
Section: Effectivenesssupporting
confidence: 89%
“…Evidence suggests that using both approaches together (standard surveillance methods (traps) and mobile apps) are effective as entomological surveillance instruments for decisionmaking in the control of Aedes mosquitoes and subsequent action. Our review shows that the most dominant purpose is surveillance while research on management of arboviral disease is limited which is consistent with another review (Abaza and Marschollek, 2017). However, we also observed an increasing interest in the use of mobile phones addressed to diagnose arboviral diseases in the last three years.…”
Section: Effectivenesssupporting
confidence: 89%
“…With regard to the success of mMHealth uptake among vulnerable Arab populations, many barriers exist spanning stigmatization, technological literacy, technological access, general distrust towards healthcare providers and political conflicts [14,28,30,35]. In Arab communities, there is a strong social stigma associated with mental illness as men who seek care are considered weak and women associate it with helplessness and being 'cursed' [12,37,38]. Another barrier is the preferred provider-patient relationship in this population, in which Arabs expect an authoritative style of communication where providers give concrete and specific solutions rather than long-term, "collaborative," dynamic psychotherapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its novelty, mHealth has had some inspiring successes that may serve as precedents for governments and NGOs around the globe. A review article by Abaza and Marschollek published in 2017 identified 255 distinct articles addressing different applications of mHealth technology [38]. These studies spanned the globe and covered all continents except Antarctica and addressed mHealth applications for chronic diseases, transplantation, dermatology, dentistry, health promotion, maternal and child health and so forth [38].…”
Section: Discussionmentioning
confidence: 99%
“…To get reliable and complete information from genomic data, sample sizes must be adequate for the specific questions asked; the centralization of samples storage collected during routine surveillance or case management at reference laboratories could help in having access to a large number of samples to analyze if the appropriate metadata are also stored appropriately ( Figure 2). Data transfer systems using mobile phone-based applications could be implemented at the different levels of the health systems for accurate and rapid transmission of information to the reference laboratories and the National Malaria Control Program [77][78][79]. Figure 2.…”
Section: Discussionmentioning
confidence: 99%